2011
DOI: 10.1525/jer.2011.6.2.23
|View full text |Cite
|
Sign up to set email alerts
|

Developing Community Partner Training: Regulations and Relationships

Abstract: While funders increasingly support research that partners with communities, community partners still must submit to a regulatory oversight structure that does not reflect their unique research ethics challenges and needs. In recognition of the importance of collaborative research endeavors, the authors engaged in a process of reconnaissance and negotiations with local community partners and research ethics boards (REBs) at the University of Michigan to begin to address the mismatch between regulatory demands a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Future public-domain HSPT programs that are designed specifically for community partners in CBPR relationships (that maintain rigorous content) may provide an even more efficient starting point for local adaptation 7 . However, we found that the success of HSPT lies not in the content, but in the implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future public-domain HSPT programs that are designed specifically for community partners in CBPR relationships (that maintain rigorous content) may provide an even more efficient starting point for local adaptation 7 . However, we found that the success of HSPT lies not in the content, but in the implementation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication suggests that a collaborate partnership is in the process of evaluating a HSPT program targeting community members engaged in research that may serve as a model for CBPR partnerships in the future 7 . In this study, we describe the implementation of an existing HSPT program by an established CBPR partnership.…”
mentioning
confidence: 99%
“…For example, a misunderstanding of CEnR may lead an IRB to harbor misgivings about the competencies of community partners and therefore require “more” rather than “more relevant” training (Dolor, Smith, & Neale, 2008; Yawn et al, 2009). This can create administrative burdens for community partners and exacerbate mistrust among all parties (Solomon & Piechowski, 2011). IRBs that are unfamiliar with CEnR may be limited in their ability to assist CEnR teams in tackling ethical problems that emerge during study design (e.g., deciding whether or not to include a control community) or project implementation (e.g., handling potential breaches of confidentiality).…”
Section: Who Needs Research Ethics Education?mentioning
confidence: 99%
“…9 Training should also ensure that participants are able to apply knowledge in real-world settings to make certain that objectives and learning translate into measurable goals and outcomes. 10 Finally, training should build capacity to ensure a positive benefit relative to the investment of time, cost, and other resources. 11 …”
Section: Aligning the CLI With Community Partners’ Needsmentioning
confidence: 99%